Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/papt.12136
|View full text |Cite
|
Sign up to set email alerts
|

Factorial structure and construct validity of an Italian version of the Fears of Compassion Scales: A study on non‐clinical subjects

Abstract: Fears of Compassion Scales have been increasingly used in clinical and research settings. The reduced Italian version of the FCS developed in this study is a valid and parsimonious instrument. Fears of receiving compassion from others and from ourselves are more powerful predictors of psychopathological symptoms than fear of giving compassion to others. Fears of Compassion Scales were correlated with both a self-report and a behavioural measure of altruism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
10
2
Order By: Relevance
“…Fear of Compassion towards Self scale (Gilbert et al, ) consists of 15 items measured on a 5‐point Likert scale, including “I feel that I don't deserve to be kind and forgiving to myself.” The original study found high internal consistency ( α = 0.85 to 0.92). Although conflicting evidence exists regarding whether or not the scale is unifactorial (Asano et al, ; Dentale et al, ), it has clinical utility for predicting symptoms (Dentale et al, ) and CFT treatment response (Kelly et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of Compassion towards Self scale (Gilbert et al, ) consists of 15 items measured on a 5‐point Likert scale, including “I feel that I don't deserve to be kind and forgiving to myself.” The original study found high internal consistency ( α = 0.85 to 0.92). Although conflicting evidence exists regarding whether or not the scale is unifactorial (Asano et al, ; Dentale et al, ), it has clinical utility for predicting symptoms (Dentale et al, ) and CFT treatment response (Kelly et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The original study found high internal consistency (α = 0.85 to 0.92). Although conflicting evidence exists regarding whether or not the scale is unifactorial (Asano et al, 2017;Dentale et al, 2017), it has clinical utility for predicting symptoms (Dentale et al, 2017) and CFT treatment response (Kelly et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with particularly low pre‐treatment vagal tone may have lower levels of self‐regulatory capacity and, therefore, more pronounced difficulties in entering and/or remaining in psychotherapy. This is particularly true for patients with high levels of fear of compassion, for whom the therapeutic relationship per se can elicit a threat response (Dentale et al ., ; Gilbert, McEwan, Matos, & Rivis, ). Recent research has investigated the association between pre‐treatment vagal tone, dropout, and residual symptoms after exposure therapy in a sample of 228 patients with panic disorder and agoraphobia (Wendt et al ., ).…”
Section: Hrv Assessment and Psychotherapy Outcomementioning
confidence: 99%
“…The results of the process of translation and back translation were satisfactory because, according to the bilingual translators, the items were semantically similar to the original English version. The translation and back translation is a widely used method (Azari et al, 2017;Dentale et al, 2017;Frayssac et al, 2017;Lin et al, 2017;McCabe, Escoto, Cruz-Ortega, Munoz-Rojas, & Gattamorta, 2017), and it was a very suitable and reliable methodology for the present study, to that observed in this region alone (Behrens et al, 2010;Rossi et al, 2017). Further, as Sao Paulo's establishments have been reported to exhibit a higher degree of food legislation fitness (Saccol et al, 2015), the present sample may have been biased.…”
Section: Discussionmentioning
confidence: 79%
“…The results of the process of translation and back translation were satisfactory because, according to the bilingual translators, the items were semantically similar to the original English version. The translation and back translation is a widely used method (Azari et al, ; Dentale et al, ; Frayssac et al, ; Lin et al, ; McCabe, Escoto, Cruz‐Ortega, Munoz‐Rojas, & Gattamorta, ), and it was a very suitable and reliable methodology for the present study, especially considering the high level of expertise of the translators, teachers, and experts in this field of research.…”
Section: Discussionmentioning
confidence: 99%